Enhancing Students’ Writing Skill By Using Clustering Technique - Ullah, Wa Ode Ritna Yuniyr; Dharma, Yokie Prasetya (Universitas Hamzanwadi, 2019)
In this research, the focus was to know the improvement of the students' skill in writing recount text especially based on the three aspects as mentioned above. After the implementation of this technique, the students' score was improved in each aspect. They also motivated when they were asking to write recount text based on the clustering that had made by them individually. The other strengths of this technique were that the students more enjoyed the processes of teaching and learning which made the classroom atmosphere became more alive, active and orderly. This method is interesting and easy to be implemented in the teaching and learning processes. In this technique, the students are excited and enjoy every activity in the class; they bring their all ability to find ideas, materials, and data to support their work in writing skill; they are eager to exchange their ideas when they do drafting; and they are more careful to write the text based on its, grammar, vocabulary, and mechanic in order to construct a good writing text. It means that by using clustering technique, the researcher and students achieved the goal in the teaching-learning process.